Benefits of Compliance with Securities Listing Standards : Evidence From the Depository Receipt Market - Sarr, Abdourahmane (IMF Working Papers; Working Paper ;, 2001)
The paper finds that costs of implementing stringent securities listing standards may exceed benefits. Depository receipts, a growing source of international equity financing, differ in types by the reporting and disclosure standards issuing firms are required to meet. For lower levels of compliance, results show that factors associated with the stage of economic development of the issuing firm's country account for the lower levels of capital raised. Incurring reporting costs to comply with higher standards may thus be inefficient. In contrast, firms choosing to meet higher reporting and disclosure standards do so because the information revealed would have a positive effect on capital raised.